Van Wyck Brooks - American Writers 71 : University of Minnesota Pamphlets on American Writers - Wasserstrom, William (Book collections on Project MUSE., 1968)
The displacement of Van Wyck Brooks from the center to the farthest margins of literary influence today is surely a stunning shift of taste. In 1920 Brooks was regarded as the undisputed heir of the great tradition in American thought-the radical, reformist, prophetic, "organic" tradition which adopted Emerson as its source of inspiration, took The American Scholar as its point of departure, and envisioned as its point of terminus a civilization in which the creative spirit, in all its social and imaginative forms, might flourish.